Favorable culture conditions for spermatogonial propagation in human and non-human primate primary testicular cell cultures: a systematic review and meta-analysis - van Maaren, Jillis; Alves, Luis F.; van Wely, Madelon; van Pelt, Ans M. M.; Mulder, Callista L. (Frontiers in Cell and Developmental Biology, 2024)
Autologous transplantation of spermatogonial stem cells (SSCs) isolated from cryopreserved testicular biopsies obtained before oncological treatment could restore fertility in male childhood cancer survivors. There is a clear necessity for in vitro propagation of the limited SSCs from the testicular biopsy prior to transplantation due to limited numbers of spermatogonia in a cryopreserved testicular biopsy. Still, there is no consensus regarding their optimal culture method. To bridge this knowledge gap, we performed a systematic review and meta-analysis of studies reporting primary testicular cell cultures of human and non-human primate origin through use of Pubmed, EMBASE, and Web of Science core collection databases. Of 760 records, we included 42 articles for qualitative and quantitative analysis. To quantify in vitro spermatogonial propagation, spermatogonial colony doubling time (CDT) was calculated, which measure the increase in the number of spermatogonial colonies over time. A general linear mixed model analysis was used to assess the statistical effect of various culture conditions on CDT.Our analysis indicates decreased colony doubling times (CDT), indicating faster spermatogonial propagation in cultures with a low culture temperature (32°C); with use of non-cellular matrices; use of StemPro-34 medium instead of DMEM; use of Knockout Serum Replacement; and when omitting additional growth factors in the culture medium. The use of various methods and markers to detect the This is a provisional file, not the final typeset article presence of spermatogonia within the reported cultures could result in detection bias, thereby potentially influencing comparability between studies. However, through use of CDT in the quantitative analysis this bias was reduced. Our results provide insight into critical culture conditions to further optimize human spermatogonial propagation in vitro, and effectively propagate and utilize these cells in a future fertility restoration therapy and restore hope of biological fatherhood for childhood cancer survivors.